Bleeker was right: Revision of the genus Cyclocheilichthys (Bleeker 1859) and resurrection of the genus Anematichthys (Bleeker 1859), based on morphological and molecular data of Southeast Asian Cyprininae (Teleostei, Cypriniformes) - Pasco-Viel, Emmanuel; Veran, Monette; Viriot, Laurent (Zootaxa, 2012)
The taxonomy within the order Cypriniformes is subject to frequent changes, thanks to the results coming from recentmolecular phylogenies that help understand the Cypriniformes tree of life previously established through morphologicalcharacters. In this paper, we focus on species belonging to the Cyprininae – the largest sub-family among Cypriniformes– and we present both morphological and phylogenetic arguments to revise the taxonomy of the genus Cyclocheilichthys.For morphological investigations, we characterized external traits as well as the postcranial skeleton and theneurocranium. For molecular phylogenies, we used four markers, both mitochondrial and nuclear, to establish aphylogenetic tree. We studied four species currently assigned to the genus Cyclocheilichthys as well as the speciesCosmochilus harmandi and Puntioplites falcifer and we show that the genus Cyclocheilichthys is non-monophyletic asCyclocheilichthys enoplos is closer to C. harmandi and P. falcifer than Cyclocheilichthys armatus, Cyclocheilichthysapogon and Cyclocheilichthys repasson. Finally, we revise the genus Cyclocheilichthys and we propose to split this genusinto two genera: genus Cyclocheilichthys with the species Cyclocheilichthys enoplos and genus Anematichthys with species Anematichthys armatus, Anematichthys apogon and Anematichthys repasson.